Hollow Li1.2Mn0.54Ni0.13Co0.13O2 micro-spheres synthesized by a co-precipitation method as a high-performance cathode material for Li-ion batteries. Issue 74 (22nd July 2016) - Li, Yanxiu; Mei, Jun; Guo, Xiaodong; Zhong, Benhe; Liu, Hao; Liu, Guobiao; Dou, Shixue
Abstract : Hollow Li1.2 Mn0.54 Ni0.13 Co0.13 O2 micro-spheres were successfully synthesized by a co-precipitation method. Abstract : Hollow Li1.2 Mn0.54 Ni0.13 Co0.13 O2 micro-spheres were successfully synthesized by a co-precipitation method. The micro-spheres deliver an initial discharge capacity of 296 mA h g −1 and a coulombic efficiency of 83.4% at a current density of 30 mA g −1 . Furthermore, the micro-spheres exhibit an excellent rate capability (150 mA h g −1 at a current density of 1500 mA g −1 ) and a high reversible discharge capacity of 227 mA h g −1 after 100 cycles at a current density of 60 mA g −1 .